Statistical Power of Within and Between-Subjects Designs in Economic Experiments - Charles Bellemare; Luc Bissonnette; Sabine Kröger (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper discusses the choice of the number of participants for within-subjects (WS) designs and between-subjects (BS) designs based on simulations of statistical power allowing for different numbers of experimental periods. We illustrate the usefulness of the approach in the context of field experiments on gift exchange. Our results suggest that a BS design requires between 4 to 8 times more subjects than a WS design to reach an acceptable level of statistical power. Moreover, the predicted minimal sample sizes required to correctly detect a treatment effect with a probability of 80% greatly exceed sizes currently used in the literature. Our results suggest that adding experimental periods in an experiment can substantially increase the statistical power of a WS design, but have very little effect on the statistical power of the BS design. Finally, we discuss issues relating to numerical computation and present the powerBBK package programmed for STATA. This package allows users to conduct their own analysis of power for the different designs (WS and BS), conditional on user specified experimental parameters (true effect size, sample size, number of periods, noise levels for control and treatment, error distributions), statistical tests (parametric and nonparametric), and estimation methods (linear regression, binary choice models (probit and logit), censored regression models (tobit).
Keywords: C80; C90; D03; 330; within-subjects design; between-subjects design; sample sizes; statistical power; experiments